DENTAL STEM CELL SOURCES AND THEIR POTENTIALS FOR BONE TISSUE ENGINEERING - Fatih ASUTAY; Ahmet H. ACAR; Ümit YOLCU; Mustafa KIRTAY; Hilal ALAN (Istanbul University, 2015)
Tissue engineering arouses excitement in all medical fields that deal with bone healing. The ultimate aim of these approaches are to shorten the healing process, obtain highly differentiated functional tissues and eliminate the need for a second surgical site required for autogenous bone grafts. Mesenchymal stem cells have been increasingly used in the experiments which were conducted in these fields and the results are promising. Dental stem cells have come to the forefront both because of their relative ease of access and also their superior characteristics. This article investigates the importance of dental stem cells for bone tissue engineering and their regeneration potentials.